2016
DOI: 10.4149/317_151013n525
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB/p65 expression before and after treatment in rectal cancer patients undergoing neoadjuvant (chemo)radiotherapy and surgery: prognostic marker for disease progression and survival

Abstract: Nuclear factor-kappaB (NF-κB), especially p65 subunit, has been associated with origin and progression of cancer as well as with the resistance to radiotherapy and chemotherapy in experimental models. The aim of the present study was to determine expression of NF-κB/p65 in tumor specimens before and after treatment of rectal cancer patients and to evaluate possible relationship between expression of NF-κB/p65 before and after (chemo)radiotherapy, other tumor characteristics and the clinical outcome. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Protein biomarkers in tissues have been extensively investigated and the findings were summarized in Table 1. These newly identified protein biomarkers are involved in pathways dysregulated by chemoradiation, including DNA repair (X-ray repair cross-complementing protein 2 (XRCC2) [58], ataxia telangiectasia mutated (ATM) [59], meiotic recombination 11 homolog A (MRE11) [59], PCNA-associated factor 15 (Paf15) [60]), cell cycle (polo-like kinase 1 (Plk1) [61], and vaccinia-related kinase-1 and -2 (VRK1 and VRK2) [62]), cell proliferation (c-MYC and proliferating cell nuclear antigen (PCNA) [63], golgi phosphoprotein 3 (GOLPH3) [64], focal adhesion kinase (FAK) [65], fibroblast growth factor receptor 4 (FGFR4) [66], and nuclear factor-κB (NF-κB) [67]), apoptosis (survivin [68], and apoptotic protease-activating factor 1 (APAF-1) and COX2 [69]), autophagy (Beclin 1 [70]), cell adhesion (Plectin-1 (PLEC1) [71] and desmoglein 3 (DSG3) [72]), cell motility (transgelin (TAGLN) [71]), and metabolism (vascular non-inflammatory molecule 1 (VNN1) [73], transketolase (TKT) and hydroxyacyl-CoA dehydrogenase (HADHA) [71], and 17-β-hydroxysteroid dehydrogenase type 2 (HSD17B2) and 3-hydroxy-3-methylglutaryl coenzyme A synthase (HMGCS2) [74]). Li et al developed a three-protein biomarker panel consisting of c-MYC, PCNA, and tissue inhibitor of metalloproteinases 1 (TIMP1) for prediction of prognosis in 329 locally advanced rectal cancer patients.…”
Section: Molecular Biomarkers In Tumor Tissuesmentioning
confidence: 99%
“…Protein biomarkers in tissues have been extensively investigated and the findings were summarized in Table 1. These newly identified protein biomarkers are involved in pathways dysregulated by chemoradiation, including DNA repair (X-ray repair cross-complementing protein 2 (XRCC2) [58], ataxia telangiectasia mutated (ATM) [59], meiotic recombination 11 homolog A (MRE11) [59], PCNA-associated factor 15 (Paf15) [60]), cell cycle (polo-like kinase 1 (Plk1) [61], and vaccinia-related kinase-1 and -2 (VRK1 and VRK2) [62]), cell proliferation (c-MYC and proliferating cell nuclear antigen (PCNA) [63], golgi phosphoprotein 3 (GOLPH3) [64], focal adhesion kinase (FAK) [65], fibroblast growth factor receptor 4 (FGFR4) [66], and nuclear factor-κB (NF-κB) [67]), apoptosis (survivin [68], and apoptotic protease-activating factor 1 (APAF-1) and COX2 [69]), autophagy (Beclin 1 [70]), cell adhesion (Plectin-1 (PLEC1) [71] and desmoglein 3 (DSG3) [72]), cell motility (transgelin (TAGLN) [71]), and metabolism (vascular non-inflammatory molecule 1 (VNN1) [73], transketolase (TKT) and hydroxyacyl-CoA dehydrogenase (HADHA) [71], and 17-β-hydroxysteroid dehydrogenase type 2 (HSD17B2) and 3-hydroxy-3-methylglutaryl coenzyme A synthase (HMGCS2) [74]). Li et al developed a three-protein biomarker panel consisting of c-MYC, PCNA, and tissue inhibitor of metalloproteinases 1 (TIMP1) for prediction of prognosis in 329 locally advanced rectal cancer patients.…”
Section: Molecular Biomarkers In Tumor Tissuesmentioning
confidence: 99%
“…Different authors have pointed out that the NF-κB pathway is associated with a poor outcome in another type of cancers: NF-κB/p65 expression was evaluated by IHC in biopsies of 50 patients with rectal cancer undergoing neoadjuvant chemo or radiotherapy and surgery. The results suggested that the high level of NF-κB/p65 is associated with shortened OS [59]. In a different study, it was reported that p50 -/mice had smaller tumors and displayed high levels of IL-12 and CXCL10.…”
Section: Discussionmentioning
confidence: 87%
“…The possibility of developing radioresistance hampers the effect of neoadjuvant radiotherapy and worsens clinical outcomes. Although there have already been many attempts to seek radiosensitivity biomarkers (7)(8)(9)(10)(11)(12), less has been known about the exact mechanisms of the development of radioresistance in rectal cancer, which is vital to improve the therapeutic effect of rectal cancer further and to develop a reliable radiosensitivity evaluation method to optimize clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%